Republic of Colombia : Improving Opportunities for Education II - World Bank (Washington, DC, 2014)
This note presents the achievements in second phase of the Programmatic Knowledge Services (PKS) for improving opportunities for education in Colombia and is the final report of the PKS series. The objective of this PKS was to provide evidence and related policy advice to enhance public sector capacity for improved education policy making for the primary, secondary, and tertiary levels and within the Science, Technology and Innovation (STI) sector. The PKS was fully aligned with the country's National Development Plan and with the Bank country partnership strategy. The PKS was a multi-year program, covering FY12-FY14 and was implemented in two phases. This note presents the actions undertaken under second phase (carried out in FY13) and closes the PKS series. The FY14 strategy for the Bank's education program will focus on new lending. Colombia's education sector does not adequately prepare people for a competitive, global labor market. Learning gains, while significant, are not as rapid as needed to set Colombia on a greater path for innovation and growth. The Ministry of Education (MEN) has been undertaking efforts to improve the quality of education at all levels and to expand coverage of secondary and tertiary education.